Escribir contra la ciudad: fotos y texto en Prosa del observatorio de Julio Cortázar - Marcy Schwartz (Cuadernos LIRICO)
Of Julio Cortázar’s many photographic projects, only in Prosa del observatorio is he both author and photographer. One of the least studied works by Cortázar, Prosa presents photos of the astronomical observatories in Jaipur and Delhi designed by Jai Singh in the eighteenth century. This article explores the verbal-visual dynamic in Prosa in the context of the urban gaze that weighs on both the verbal and the visual discourse. The Western, Parisian perspective comes up against the Asian perspective of Jaipur to undermine the urban imperative.